Combined experimental/theoretical study on d-glucosamine promoted regioselective sulfenylation of indoles catalyzed by copper. (12th October 2017) - Ge, Xin; Sun, Fengli; Liu, Xuemin; Chen, Xinzhi; Qian, Chao; Zhou, Shaodong
Abstract : A combined experimental/theoretical investigation on thed -glucosamine promoted sulfenylation of indoles at the C3 position with sodium sulfinates catalyzed by copper is presented. Abstract : A combined experimental/theoretical investigation on thed -glucosamine promoted sulfenylation of indoles at the C3 position with sodium sulfinates catalyzed by copper is presented. The C3-sulfenylation of indoles shows good functional-group tolerance and yields. The 3-I-indole was identified as a crucial intermediate in the catalytic cycle. The catalytic role of [Cu(DMSO)2 ] 2+ was addressed using quantum chemical calculations. In the interaction of [Cu(DMSO)2 ] 2+ with indole, the [Cu(DMSO)2 ] 2+ complex abstracts a hydrogen from the C3 of indole. The electronic origin for selective C–H bond activation of indole was revealed.